Mengkaji Sistem Pemasaran Garam di Madura - Prasetyo Nugroho; Aprilina Susandini; Darul Islam (MediaTrend, 2020)
Salt is one of the commodities that are needed in daily life. In addition toconsumption needs, salt is needed in the industrial sector. Salt production isseasonal so it is very vulnerable to price pressures at harvest time. Prices willtend to decrease dramatically at harvest time, but will not improve when it is notthe salt season. The problem of salt in the marketing aspects of the salt tradingsystem is unclear and the dependence of farmers on middlemen.Research on salt marketing in Madura is interesting to be studied further,considering that Madura is the largest salt producer in Indonesia and all districtsin Madura produce salt. This study aims to determine the mechanism of saltmarketing in Madura. In addition, this research is expected to be able to describethe condition of the salt market structure in Madura.This study uses a qualitative approach, because it leads to a detailed andin-depth description of salt marketing conditions that occurred in Madura.Respondents in this study are salt farmers and other parties involved in saltmarketing in Madura.From the study, we have results that show all the parties involved in thesalt marketing chain in Madura i.e. (a) salt farmers and PT. Garam (Persero) as alocal salt producer; (b) traders or middlemen; (c) processing companies orfactories; (d) distributors who distribute processed salt to consumers or tocompanies that use salt as a supporting material; (e) retailers or retailers. In themarketing system, salt farmers have a weak bargaining position.